Heat and mass transfer regimes for room cooling and dehumidification using chilled water radiators - Hirayama, Y. (Cranfield University, 1998)
The application of room radiators for the purposes of cooling and dehumidification in buildings for hot and humid climates is investigated. The radiator is purposely brought below the dew point temperature of the room air thereby creating condensation on the radiator surface. The condensate is then collected at the base of the radiator and removed. Mathematical models describing the heat transfer regime within a room when this system is used have been verified using climate chamber tests. The models show good agreement with the experimental results for radiator (a) with a height of 1 m, but not as accurate for radiator (b) with a height of 2 m. The underestimation of the real values by the convective heat transfer model used for the geometric construction of the radiator tested is attributed to the effect of air entrainment along the height of the radiator. Results indicate the importance of the radiant transfer component of the radiator, as well as its effectiveness to remove latent heat. In view of improving thermal comfort and energy efficiency, the implication of the results from this investigation of the heat transfer characteristics of the radiator used for cooling and dehumidification is such that the chilled radiator may offer a definite alternative to conventional air conditioning systems. Partial or full matching of the sensible and latent component of the radiator output to the load requirements of a building should prove particularly effective in hot and humid regions where the latent heat factor of the total cooling load is high.